An efficient LC-QTOF-mass spectrometry method for monitoring naltrexone compliance in urine of opioid-dependent subjects - Jain, Raka; Mandal, Piyali; Rana, Sachin (Journal of Opioid Management, 2024)
Naltrexone (NTX) is an orally effective opiate antagonist used in maintenance treatment for opiate dependence. Its utility is limited by the patient’s noncompliance. The study aimed to develop an efficient method for the detection of NTX in urine by LC-QTOF-mass spectrometry (MS) and its application to NTX compliance in opioid-dependent subjects. Sample preparation included a dilution step and direct injection to LC-QTOF-MS. Chromatographic separation was achieved with a C-18 column using a mixture of mobile phase 0.1 percent formic acid in water and 0.1 percent formic acid in 95 percent methanol. The calibration curve was linear in the range 1-100 ng/mL with a correlation coefficient higher than 0.996. Precision and accuracy were acceptable, and the recovery efficiency range was 80-85 percent. The current LC-QTOF-MS method is simple, precise, sensitive, and can be used for monitoring NTX compliance among opioid-dependent subjects in a clinical setting.